2012
DOI: 10.15376/biores.7.4.5304-5311
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Temperature and Moisture Profiles of Wood Exposed to Infrared Radiation

Abstract: In this article we studied the mechanism of wood drying using infrared (IR) heat transfer. Norway spruce (Picea abies (L.) Karst.) samples of 50 mm and 200 mm thickness were exposed to IR radiation, and the temperature and moisture profiles were recorded at the surface and at the core of the samples under controlled experimental conditions. It is proposed that the moisture transport in wood during drying is governed by osmotic effects. Based on such a hypothesis, the temperature stagnation was explained by a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Infrared emitters consisting of an energy source and a reflector provide deep or surface heating of the irradiated body or, if necessary, local drying of the object. This type of wood drying is not widely used due to the low degree of penetration of infrared waves into the object [2].…”
Section: In Order To Generalize the Possibilities Of Using Mw Radiatimentioning
confidence: 99%
“…Infrared emitters consisting of an energy source and a reflector provide deep or surface heating of the irradiated body or, if necessary, local drying of the object. This type of wood drying is not widely used due to the low degree of penetration of infrared waves into the object [2].…”
Section: In Order To Generalize the Possibilities Of Using Mw Radiatimentioning
confidence: 99%
“…The choice of IR technology was also motivated by the potential ease with which IR heaters could be integrated into peeling machines and by the power it offers, which enable a rapid heating, in line with the high peeling speeds (from 1 to 5 m s Previous studies have demonstrated the ability of IR radiation to raise the temperature of the surface and the layers below either for heating ( Makoviny and Zemiar 2004 ) or for drying ( Cserta et al 2012 ). With heating source flux densities of 126 kW m -2 , surface temperatures of 50 ° C can easily be achieved by IR heating in green logs of beech, Douglas fir, and okoum é with peeling speeds of 0.25 -0.5 m s -1 ( Coste 2005 ; in this case, the logs should be defreezed and the IR flux densities were low (4 -20 kW m -2 ) ( B é dard and Lagani è re 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar measurements applied to oak at moisture contents of between 0 and 20 % suggested that in all probability, the penetration depth of IR was less than 0.1 mm (Makoviny and Zemiar 2004). However, with this method, it remains difficult to precisely evaluate heat absorption into wood by radiation because the measurement techniques are necessarily biased by heat transfer through conduction (Cserta et al 2012). Recent developments in IR spectroscopy have yielded more precise estimates of IR penetration into wood.…”
Section: Introductionmentioning
confidence: 99%